Design and Fabrication of a Strip and Slice Pickled Bamboo Shoot Slicing Machine: Design and Fabrication of a Strip and Slice Pickled Bamboo Shoot Slicing Machine - อินทรีย์มีศักดิ์, บัณฑิต; เลิศโกวิทย์, พิพัฒน์ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2019)
The research aims to design and fabrication of a strip and slice pickled bamboo shoot slicing machine which is the agriculturist have problems in the production process. It took a lot of time and was dangerous while slicing bamboo from the sharpness of a knife. The principle of this projected was design and construct all component of the machine with a Solid work simulation program. The machine includes 2 sets of AC.Motor, 0.5 hp.,220 Vac 1450 rpm. to drive knife blade rotor, and the second motor was Electrical Gear Motor,0.5 hp., 220 vac. with the ratio 1:70 or 20 rpm. to drive conveyor modular belts with a set of inverter to control speed. The results show that capable of slicing 10 kg. of bamboo shoot with human labor at average time of 62.08 minutes compared with bamboo shoot slicing machine intend speed of knife edge at 400, 500, 600, 700, 800 rpm respectively. The test from machine separated in 2 parts, first slice in noodle shape of 3 mm. thick, the best quality was at 700 rpm. with average time of 20.44 minutes and slice in sheet shape of 2 mm. thick, the best quality was at 800 rpm. with average time of 25.31 minutes